Animal Names and Animal Classifications in Mesopotamia: An Interdisciplinary Approach Based on Folk Taxonomy - Wapnisch, Paula Claire
Ph. D. diss.; Order No. DA 8511567. Cf. DissAbstr 46 (1985) 693-A.